Partial-photoelectron-wave analysis in diatomic molecule photoionization by fluorescence polarization experiments - Demekhin, Philipp V.; Petrov, Iwan D.; Ehresmann, Arno (Physical review. A, Atomic, molecular, and optical physics, 2010)
Parameters β1 and β2 describing the angular distribution of circularly polarized fluorescence photons emitted by randomly oriented diatomic molecules excited by circularly polarized radiation are derived. We prove theoretically that measuring these parameters allows a partial-wave analysis of the emitted photoelectrons in the case of closed-shell diatomic molecules. The determination of the relative partial cross sections for emission of the ɛσ, ɛπ, and ɛδ photoelectrons is of fundamental importance for a sensitive test of corresponding calculations.